BRIEF REVIEWS OF THE HISTORY OF THE STUDY OF MERCURIES - Temirova Munira Amirqulovna (Scholar Express Journal, 2021)
This article provides information on the "mercury" pottery product, which was widespread in the Middle Ages, and its construction and function. We will also consider M.F.de Solsi, who also worked on the subject, Vivant Denon, F.I, the research of Ouspensky, VL Vyatkin and others. We will also discuss versions of the mercury-containing lamp, grenade, and mercury storage container
Keywords: as a grenade; fish-like base; perfume container; liquid mercury